Pengaruh Gaya Kepemimpinan, Komitmen Organisasi, Dan Kompetensi Pendamping Desa Terhadap Penerapan Good Village Governance (Studi Kasus Pada Desa Di Kabupaten Buleleng) - luh novi bamyanti; Nyoman Ayu Wulan Trisna Dewi (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of leadership style, organizational commitment, and competence of village assistants on the implementation of good village governance. This type of research is quantitative research. The population used is the village apparatus, namely the village head, secretary, and treasurer in villages in Buleleng Regency. The sampling technique used in this study was the probability sampling method, namely proportional random sampling. The source of the data used is primary data using a questionnaire which is measured using a Likert scale. Analysis of the data used in this study using descriptive analysis, data quality test, classical assumption test, and hypothesis testing using the statistical Package for Social Science (SPSS) v.20 programs. The results of the study show that (1) leadership style has a positive and significant effect on the implementation of good village governance; (2) organizational commitment has a positive and significant impact on the implementation of good village governance; and (3) the competence of village facilitators has a positive and significant impact on the implementation of good village governance. Keywords: leadership style, organizational commitment, the competence of village assistants, and good village governance